Challenges and Efforts of Environmental Management Toward Smart Environment in Ternate - Lely Adriani Nasution; Yuni Andriyani Safitri; Eva Marthinu; Rohana Sufia (Universitas Lambung Mangkurat, 2025)
The implementation of the smart city concept involves the creation of a city that is digitally integrated. As a result, cities designated as smart cities undergo transformation, facing various challenges and efforts, particularly in environmental management. Ternate is one such city that is transforming its environmental management practices to develop a smart city focused on a smart environment. This research was conducted qualitatively, gathering data through focus group discussions (FGDs) and in-depth interviews with community members and relevant government agencies involved in implementing smart environmental initiatives. The findings indicate that the primary environmental challenge facing Ternate is waste management. Issues include low public awareness regarding proper waste disposal, a limited number of waste collection vehicles, and inadequate waste management and processing facilities. To address these challenges, it is essential to implement initiatives such as community outreach regarding waste banks, increasing the number of waste collection vehicles, and exploring collaborative opportunities with other parties to enhance waste management and processing in Ternate.